MARKETING OF EDUCATION BUSINESS TO RESPOND TO THE NEEDS OF GEN Y CONSUMERS: A CASE STUDY OF SMART BRAIN FRANCHISE BUSINESS IN SA KAEO PROVINCE - Tulachom, Jidapa; Tresirichod, Teetut (RMUTT GLOBAL BUSINESS ACCOUNTING AND FINANCE REVIEW, 2021)
The study attempts to study marketing of education business to respond to the needs of and to compare marketing of education business to respond to the needs of Gen Y consumers. The population in this study were 380 parents of Gen Y consumers using questionnaire as the research tool. Computer software program was utilized to analyze the data and the statistics used were frequency, percentage, average, standard deviation, stepwise multiple regression analysis, and One Way ANOVA. The findings revealed that: 1) The personal factors of Gen Y consumers in Sa Kaeo Province found that the majority were lower Gen Y (age of 25-29 years old), follow with upper Gen Y (age of 30-34), and teenager Gen Y (age of 15-24), respectively; 2) The study on marketing of education business responding to the needs of Gen Y consumers shows that the majority of the subjects thought that place for distribution and after-sales service should be utilized, follow with the product design, establishing the brand, and marketing; 3) Distinguish characteristics of Gen Y consumers that business sector should emphasize involving selected consumers and flexible to technology at the percentage of 46; and 4) When comparing marketing of education business to respond to the needs of Gen Y consumers classifying by sub-groups of Gen Y consumers, it was found that Gen Y consumers expressed their thought toward marketing of education business to respond to the needs of Gen Y consumers with no statistically significant level.